Togo : Fifth Review under the Extended Credit Facility Arrangement-Press Release; Staff Report and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report ;, 2020)
The economic recovery seems to be taking hold. Inflation stood at 0.6 percent at end-July 2019. The fiscal consolidation was sustained through the first half of 2019; the overall fiscal deficit is estimated at 0.2 percent of GDP at end-June 2019. Reforms are progressing on revenue and customs administration as well as public expenditure management. While the authorities are committed to privatize the two public banks, the tenders for both banks were launched with a delay in September 2019 (prior action). Socio-political tensions have abated but uncertainty remains high, particularly considering the presidential election scheduled for 2020.